At Least a Fish - Anushka Ravishankar (India Scholastic India Pvt Ltd, 2017)
Zain and Ana lead a life riddled with anxieties and questions. Do fish like spinach? Is the dragon in the pond lonely? If you dig a hole that s deep enough, will you fall right through to China? Can magic medallions make you invisible? Rambling through random and exciting childhood event's, these books are about the mad adventure of being children. The thin line dividing fantasy and reality is crossed and recrossed as dumb dogs, nosy twins, dead fish and live dragons wander in and out of the world of Zain and Ana. The first book in the series at Least a Fish is about what happens when Ana asks for a puppy.
Keywords: Fiction -- Fiction